Peer inter-laboratory validation study of a harmonized SPME-GC-FID method for the analysis of selected volatile compounds in virgin olive oils. (May 2021) - Casadei, Enrico; Valli, Enrico; Aparicio-Ruiz, Ramón; Ortiz-Romero, Clemente; García-González, Diego L.; Vichi, Stefania; Quintanilla-Casas, Beatriz; Tres, Alba; Bendini, Alessandra; Toschi, Tullia Gallina
Abstract: In the context of supporting the panel test in the classification of virgin olive oils, the qualitative and quantitative analysis of a number of volatile compounds responsible for their aroma is of great importance. Herein, the data obtained from three laboratories that analyzed the same samples are presented with the view to develop an inter-laboratory validation study of a harmonized solid-phase micro-extraction coupled with gas-chromatography with flame ionized detector (SPME-GC-FID) method for determination of selected volatile compounds. In particular, quantification of the minimum number of key markers responsible for positive attributes (e.g. fruity) and sensory defects was investigated. Three quantification strategies were considered since they can have a notable impact on the effectiveness of the use of markers as well as on the robustness and simplicity of the method that is designed for control laboratories. A peer-validation study indicated repeatability with a mean relative standard deviation (RSD%) lower than 14% except for ethyl propanoate, 3-methyl-1-butanol, 1-octen-3-ol, and ( E )-2-decenal. Linearity was satisfactory (R 2 > 0.90) for all compounds when the calibration curves were corrected by the internal standard. Several critical issues were identified, such as high RSD% (>50%) in terms of reproducibility for ethyl propanoate, ( E )-2-decenal, and possible improvements of the limits of detection (LODs) and quantitation (LOQs) of ( E )-2-heptenal, ( E, E )-2, 4-hexadienal, and ( E )-2-decenal. In particular, some compounds (ethyl propanoate, ( E )-2-heptenal, 1-octen-3-ol, ( E, E )-2, 4-hexadienal, ( E )-2-decenal and pentanoic acid) showed LOQs that were higher than the concentrations found in some samples. The discussion permitted improvement of the protocol towards the final version for an upcoming full validation process. Highlights: SPME-GC-FID method was validated (3 labs) for analyzing 18 virgin olive oil VOCs. R 2 was >0.90 when the internal standard was used to build the calibration curves. Mean RSD% for repeatability was <14% for 14 out 18 compounds. Mean reproducibility RSD% was high (>50%) for ethyl propanoate and ( E )-2-decenal. LODs/LOQs were studied and the results discussed with respect to S/N ratio.